To The Question Of Allocation Of Verbs Of Intellect Activity In Lexical And Semantic Group - Samosenkova, Tatyana (2018)
This article is devoted to justification of intellect activity verbs allocation in separate lexico-semantic group of verbs on the basis of semantic similarity, thematic unity, distributive uniformity and word-formation potential. The grammatical peculiarity of the verb requires special linguistic methods for its study. Relevance of the question considered in the article is caused by complexity of the lexical and grammatical nature of verbs of intellect activity, their frequency and prevalence in different functional styles of the speech, as well as by absence of their complex description accounting the last achievements of linguistics.